Asymptomatic Hemangioma of the Duodenum - Thomas, Tristan; Haney, Michael; Doepker, Matthew (Edelweiss Applied Science and Technology, 2018)
Hemangiomas of the small bowel are exceedingly rare benign tumors. When diagnosed they are found in the setting of an acute gastrointestinal bleeding, but can also be involved in intussusception, obstruction, and cause pain. There are few reports of this case over all, and incidental or asymptomatic cases are rare for adult patients. Although computed tomography with angiography or tagged red blood cell scans are pivotal for acute active bleeding, endoscopy has become pivotal in diagnosis of lesions that are quiescent. Management is also variable as endoscopy, laparoscopy, and open surgery have all been utilized with success.